PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PERATURAN WALIKOTA PEKANBARU NOMOR 74 TAHUN 2020 TENTENG PEMBATASAN SOSIAL BERSKALA BESAR DALAM RANGKA PERCEPATAN PENANGANAN CORONA VIRUS DISEASE (COVID-19) DI KOTA PEKANBARU - Aditya Sofyan Mahendra; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the spread of covid-19 in Indonesiawhich is increasing and expanding across regions and across countries accompanied bythe number of cases or the number of deaths. Likewise, as happened in the city ofPekanbaru, 1,174 were confirmed positive for the corona virus (Corona.Riau.go.id).This increase has an impact on the political, educational, economic, social, cultural,defense and security aspects, as well as the welfare of the community. Theimplementation of health quarantine is a joint responsibility of the Central Governmentand the Pekanbaru City Government as a form of protection for public health fromdisease or public health risk factors so that the COVID-19 outbreak and public healthemergency can be overcome immediately. Health quarantine is carried out throughobservation of diseases and public health risk factors for transportation means, people,goods, and/or the environment. As well as quarantine in the form of Large-Scale SocialRestrictions (PSBB). This research method is descriptive quantitative, the datacollection instruments used in this research are questionnaires, interviews anddocumentation. The variable of this research is Riau University Student Perceptionwhich consists of 11 indicators with a total of 27 questions based on ResearchInstruments. The population in this study were Riau University students with a totalpopulation of 32,436 people. Sampling from the entire population was taken using theQuota Sampling technique and to determine the respondents consisting of 10 peoplefrom each faculty at the University of Riau researchers used the Incidental Samplingsampling technique. Based on the results of research and recapitulation that has beencarried out by researchers, respondents who answered Strongly agree (SS) + Agree (S)42.4% + 41.8% = 84.2%. Thus, it can be concluded that the perception of RiauUniversity students towards the Pekanbaru mayor's regulation number 74 of 2020regarding large-scale social restrictions in the context of accelerating the handling ofCOVID-19 in Pekanbaru City is at 75.01% - 100% and is categorized as Very Good.Key Words: Student,perceptios,, large-scale social restrictions